Kontribusi Kepemimpinan Transformasional, Motivasi Kerja, Etos Kerja, dan Kepuasan Kerja Terhadap Kinerja Guru di SMK Negeri 1 Denpasar - G.A. Wijaya -; I.M. Yudana; A.A.G. Agung (Pascasarjana Universitas Pendidikan Ganesha, 2021)
This study focused on the study of the contribution of (1) transformational leadership to the performance of the teachers of SMKN 1 Denpasar, (2) work motivation to the performance of the teachers of SMKN 1 Denpasar, (3) work ethic to the performance of SMKN teachers. 1 Denpasar, (4) job satisfaction to the performance of teachers at SMKN 1 Denpasar, (5) transformational leadership, work motivation, work ethic, and job satisfaction to the performance of teachers at SMKN 1 Denpasar. This study used an ex post facto design involving 36 teachers from 137 teachers in SMKN 1 Denpasar. The data were collected using a questionnaire. The data obtained were analyzed by multiple regression analysis. The results show (1) there is a significant contribution between transformational leadership to teacher performance, (2) there is a significant contribution between work motivation and teacher performance, (3) there is a significant contribution between work ethic and teacher performance, (4) there is a contribution which is significant between job satisfaction on teacher performance, (5) simultaneously there is a significant contribution of transformational leadership, work motivation, work ethic, and job satisfaction to teacher performance. Among the four predictor variables studied, all of them affect teacher performance so that the logical consequence is to improve teacher performance by increasing the value of transformational leadership, work motivation, work ethic, and job satisfaction. Reviewing the contribution of different influences, the most influential predictor is work ethic (X3) of 41.87%, this predictor should be prioritized to improve teacher performance optimally.